2009
DOI: 10.1002/hipo.20714
|View full text |Cite
|
Sign up to set email alerts
|

Associative recognition and the hippocampus: Differential effects of hippocampal lesions on object‐place, object‐context and object‐place‐context memory

Abstract: The hippocampus is thought to be required for the associative recognition of objects together with the spatial or temporal contexts in which they occur. However, recent data showing that rats with fornix lesions perform as well as controls in an object-place task, while being impaired on an object-place-context task (Eacott and Norman (2004) J Neurosci 24:1948-1953), suggest that not all forms of context-dependent associative recognition depend on the integrity of the hippocampus. To examine the role of the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
202
3
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(221 citation statements)
references
References 54 publications
14
202
3
2
Order By: Relevance
“…Previous studies have demonstrated that recognition memory can be impaired by lesions on the PFC in monkeys and rats (Bachevalier andMishkin, 1986, Kolb et al , 1994). On the other hand, studies in rodents showed contradictory results regarding the implication the hippocampus in recognition memory, reporting that hippocampal lesions may have no effect in object recognition memory in rats (Forwood et al , 2005, Langston and Wood, 2010, Mumby et al , 2002. This suggests that the PFC may have a more influential role in recognition memory compared to the hippocampus in rodents.…”
Section: Bardoxolone Methyl Prevented Hf Diet Induced Decline In Downmentioning
confidence: 99%
“…Previous studies have demonstrated that recognition memory can be impaired by lesions on the PFC in monkeys and rats (Bachevalier andMishkin, 1986, Kolb et al , 1994). On the other hand, studies in rodents showed contradictory results regarding the implication the hippocampus in recognition memory, reporting that hippocampal lesions may have no effect in object recognition memory in rats (Forwood et al , 2005, Langston and Wood, 2010, Mumby et al , 2002. This suggests that the PFC may have a more influential role in recognition memory compared to the hippocampus in rodents.…”
Section: Bardoxolone Methyl Prevented Hf Diet Induced Decline In Downmentioning
confidence: 99%
“…We defined exploration as sniffing or touching the stimuli objects with the muzzle and/or forepaws. A discrimination index (DI = (Time exploring novel object À Time exploring familiar object)/Total object exploration time) was used as a measure of discrimination between familiar and novel objects (Aggleton, Albasser, Aggleton, Poirier, & Pearce, 2010;Aubele, Kaufman, Montalmant, & Kritzer, 2008;Langston & Wood, 2010;Cohen et al, 2008;Till et al, 2015). DI varies between À1 and +1.…”
Section: Behavioral Procedures and Data Analysismentioning
confidence: 99%
“…While a number of studies show that hippocampal or fornix lesions produce no effect in object recognition (Bussey et al, 2000;Mumby et al, 2002;Winters et al, 2004;Forwood et al, 2005;Good et al, 2007;Langston and Wood, 2010), other studies report significant impairments (Clark et al, 2000(Clark et al, , 2001). In contrast, object-in-place memory is impaired following fornix lesions (Bussey et al, 2000) and hippocampal lesions impair temporal order discriminations (Kesner and Novak, 1982;Chiba et al, 1994;Vorobyov, 1998;Fortin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%